Civilizational Identity
XIII, 243 p.
Keywords: This volume focuses on the constitutive politics of civilizational identity, examining the practices through which notions of civilizational identity are produced and reproduced in different contexts, including the global credit regime, modernity debates, and the "war on terrorism".